Correlation between pulmonary function and six minutes walk test with computed tomography severity score in post COVID patients - Rampradeep, Rishab; G., Prasanth; V., Gangadharan (International Journal of Advances in Medicine, 2023)
Background: The current global pandemic of the coronavirus severe acute respiratory syndrome coronavirus 2 is the world’s most critical ongoing healthcare problem, with 8.2% of critically ill patients developing acute respiratory distress syndrome and requiring Intensive care unit admission. Our study aimed to correlate CT severity score of the patient at the time of diagnosis with spirometry, 6-minute walk test and breath holding time at 12 weeks after discharge, to determine the nature of residual pulmonary dysfunction and if CT severity was a predictor of poor lung function post recovery. Methods: Ambi-directional single center study conducted in Saveetha medical college Hospital, Chennai. Patients over the age of 18 with a positive COVID-19 RTPCR report and a CTSS>1 were enrolled into the study, and a sample size of 50 patients was taken after systematic random sampling. PFT, 6-minute walk test and Breath Holding Time were done at 12 weeks post discharge. Results: Mean CT severity score was: 11.48. 26% of the patients had more than 50% lung involvement on CT. There was significant negative correlation observed between FVC and Severity score (r=-0.366, p=0.009) and Breath holding and Severity score (r=-0.339, p=0.016) while there was no significant correlation between 6-minute walk test and CT Severity. Conclusions: Patients with significant lung involvement during SARS-COV-2 infection showed impaired pulmonary function test parameters in the form of a reduced FVC and breath holding time, 3 months following diagnosis. Long-term follow up and pulmonary rehabilitation is crucial to achieve respiratory recovery.